SPIRAPRIL IN TREATMENT OF HEART FAILURE DUE TO DILATED CARDIOMYOPATHY - T. A. Abdullaev; E. V. Kiyakbaeva; N. A. Kurbanov; I. R. Prohorova; R. S. Bekbulatova (Российский кардиологический журнал, 2002)
Spirapril in treatment of heart failure due to dilated cardiomyopathy.